Palliative care training programmes for community volunteers working with children and their families: a scoping review - Ontrakrai, Nattaporn; Bailey, Cara; Valler, Tracey; Neilson, Susan (Frontiers in Public Health, 2025)
IntroductionVolunteers play a significant role in enhancing the quality of palliative care. Training is necessary to deliver voluntary community care that assists healthcare professionals, benefits families and eradicates inequities for underserved populations. Community volunteers form a large part of paediatric palliative care support, but training courses are rarely specific to children leaving volunteers unprepared and unsupported.AimTo identify existing literature and synthesise knowledge gaps related to volunteer training in community paediatric palliative care.MethodThis scoping review was guided by Arksey and O'Malley and Levac et al. We conducted searches for published literature on palliative care education published between 2000 and 2023 through comprehensive searches of the Web of Science, CINAHL Plus, MEDLINE, PsycINFO, Scopus, and Cochrane Library databases.ResultsIn total, 16 (out of 590) articles met the eligibility criteria and were extracted for review. No articles exploring paediatric palliative care training for community volunteers were identified but findings from research with adults suggest that training should be tailored to volunteers' responsibilities, local needs, and culture. Training is varied but volunteers will likely benefit from blended learning that engages with communities. Four predominant domains were identified: public health palliative care education, factors related to developing community volunteers, main topics and training contents, and training models for community volunteers.ConclusionsGlobally, the provision of palliative and end-of-life care is increasingly falling to carers, volunteers, and public health workers. Education is vital to prepare volunteers, improve confidence and offer support. This first scoping review of volunteer training provides much-needed evidence to guide future educational development for the informal workforce and identifies a gap for original research specific to paediatrics.